TRANSFORMATION IN TRANSLATION: THE ROLE OF DISCOURSE MARKERS IN ENGLISH AND UZBEK - Safoyeva Sadokat Nasilloyevna (Web of Journals Publishing, 2025)
Translation is more than a mere transformation of words from one language into another; it is an evolving process that involves adjusting linguistic, cultural, and contextual factors. This research considers how discourse markers (DMs) change during translation from English to Uzbek with an emphasis on their retention, omission, or replacement. Through the analysis of translated texts, the study demonstrates how these changes affect coherence and general meaning. Also, this study investigates the impact of changes in discourse markers on readability and maintenance of meaning, with particular focus on the translator's decisions in different text environments.
Keywords: Discourse, transformation, linguistics, retention, substitution, omission, equivalence, textual, contextual, interpretation.